2019
DOI: 10.1103/physreva.100.032708
|View full text |Cite
|
Sign up to set email alerts
|

Quasiclassical method for calculating the density of states of ultracold collision complexes

Abstract: We derive a quasiclassical expression for the density of states (DOS) of an arbitrary, ultracold, N -atom collision complex, for a general potential energy surface (PES). We establish the accuracy of our quasiclassical method by comparing to exact quantum results for the K 2 -Rb and NaK-NaK systems, with isotropic model PESs. Next, we calculate the DOS for an accurate NaK-NaK PES to be 0.124 µK −1 , with an associated Rice-Ramsperger-Kassel-Marcus (RRKM) sticking time of 6.0 µs. We extrapolate the DOS and stic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
132
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(154 citation statements)
references
References 28 publications
10
132
3
Order By: Relevance
“…Mayle et al obtain the RRKM sticking time using multichannel quantum defect theory (MQDT) [ [25,26], which treats the long range fully quantum mechanically but uses a simplified short range, parametrized by the DOS. However, in the accompanying paper [28] we show that there was an error in the DOS calculation, leading to sticking times of 2 to 3 orders of magnitude too large. A quasiclassical equation to accurately calculate the DOS for arbitrary potentials is found…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…Mayle et al obtain the RRKM sticking time using multichannel quantum defect theory (MQDT) [ [25,26], which treats the long range fully quantum mechanically but uses a simplified short range, parametrized by the DOS. However, in the accompanying paper [28] we show that there was an error in the DOS calculation, leading to sticking times of 2 to 3 orders of magnitude too large. A quasiclassical equation to accurately calculate the DOS for arbitrary potentials is found…”
mentioning
confidence: 81%
“…These calculations result in a DOS of 0.37 μK −1 (for J ¼ 1) and a sticking time of about 18 μs. We showed that this lifetime is not long enough for complex-diatom collisions to explain the experimental losses [28].…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Christianen et al predict a lifetime for the (RbCs) 2 complex of 0.253 ms [50]. Their prediction is extrapolated from a detailed calculation for (NaK) 2 using approximate scaling laws.…”
mentioning
confidence: 99%